AFLATOXIN CONTAMINATION IN CHILGOZA PINE NUTS (Pinus gerardiana Wall.) COMMERCIALLY AVAILABLE IN RETAIL MARKETS OF JAMMU, INDIA - SUMEDHA SHARMA; DIMPLE GUPTA; Y.P. SHARMA (International Journal of Pharma and Bio Sciences, 2013)
The aim of the present investigation was to check natural aflatoxin contamination and aflatoxigenic potential of Aspergillus flavus strains isolated from chilgoza pine nuts. Fifty eight samples of chilgoza pine nuts, randomly purchased from retail shops and local markets of different locations of Jammu, were subjected to mycological analysis for isolation of Aspergillus flavus isolates using standard blotter method. A total of 35 isolates were recovered during mycological analysis of these nuts. Of these 25.71% isolates were aflatoxigenic, producing aflatoxin B1 and B2 in varying amount. Natural contamination of aflatoxins was detected in 46.55% of investigated samples (58) with a mean range of 0.737±0.023-1.675±0.486µg/g, which is quite high in comparison to maximum tolerable limits of 4µg/kg set forth by the European Union Commission for ready to eat nuts. The present study is the first report on the incidence of aflatoxin contamination in chilgoza from the markets of Jammu, India.